If it's not what You are looking for type in the equation solver your own equation and let us solve it.
0.12x+0.5(x-5)=0.01(4x-3)
We move all terms to the left:
0.12x+0.5(x-5)-(0.01(4x-3))=0
We multiply parentheses
0.12x+0.5x-(0.01(4x-3))-2.5=0
We calculate terms in parentheses: -(0.01(4x-3)), so:We add all the numbers together, and all the variables
0.01(4x-3)
We multiply parentheses
0.04x-0.03
Back to the equation:
-(0.04x-0.03)
0.62x-(0.04x-0.03)-2.5=0
We get rid of parentheses
0.62x-0.04x+0.03-2.5=0
We add all the numbers together, and all the variables
0.58x-2.47=0
We move all terms containing x to the left, all other terms to the right
0.58x=2.47
x=2.47/0.58
x=4+0.15/0.58
| 26x-5x-3+4=40 | | -4(x+3)+57=35 | | -4(x+3)+5-7=35 | | -x=2=x-5-3x | | 15x+12=3x+36 | | 3(3x+2)-x=2(2+3) | | 4n+18=5n+27 | | 4•x-6=3•x+5 | | 4(7+2x)=57-(x-6) | | 4x-8+x+2=180 | | 2k-2=-13-3k | | m/9-1/2=5/18 | | 4x-2-2x=5 | | 48t^2-147=0 | | -7(m-8)=3m+16 | | -9x+x=72 | | -8+p=p-8 | | 3x=9-5x-13 | | 7x+9-4x=2(x=5) | | -2z=-5z-24 | | X*(x-24)=1200 | | 3/4(12x+1.6)-2x=22.2 | | -4x(8+7)=-10-6x | | 9-5x-13=9-5x | | 30x27=-45x-6 | | 0.5z+3.8=4.9z-0.6 | | 2r-4=2r+10 | | −8x3=(7x6−3x5) | | -5x=-40+-3x | | -2/7=1/6-3/4q | | .6x=3.3 | | 16/7x=0 |